Epithelioid hemangioendothelioma of the craniocervical junction; case report and review - Ali Ender Ofluoglu; Mehmet Aydogan; Uzay Erdogan; Onder Ofluoglu (Acta Orthopaedica et Traumatologica Turcica, 2017)
Epithelioid hemangioendotheliomas are uncommon vascular neoplasms and their spinal location is even rarer. We report clinical course of a 31-year-old man with an epithelioid hemangioendothelioma at the cranio-cervical junction. A cervical magnetic resonance imaging revealed tumor that caused posterior cervical cord compression. C1,2,3 total laminectomy and surgical excision of the tumor was performed. Postoperative external beam radiation was performed on the surgical field especially around the right vertebral artery. At 2-year follow-up there was no neurological deficit and no tumor recurrence. Keywords: Epithelioid hemangioendothelioma, Craniocervical junction, Surgical excision